Preoperational Development of Eearly Childhood with Insectarium Media - Ranny Fitria Imran; Novi Ade Suryani (LPPM Universitas Pahlawan Tuanku Tambusai, 2018)
Golden age is an investment for the future that is at the age of 2-7 years. This study, trains child development at the pre-operational stage of early childhood because children are still thinking realistic. To train early childhood development, this study uses insect-resistant media, which serves to introduce early childhood to surrounding insects. The research method used is the Pre Test Post Test Group Design. The subjects of this study were children of group B of Rafa PAUD in Bengkulu City. Data collection in this study is the initial test (pretest) and final test (posttest). From the results of the pretest of children's ability, there are still undeveloped children and the results of the post-test there are 7 well-developed children. The conclusion of this study is the use of insect-resistant media (insectarium) influences the preoperational thinking abilities of early childhood group B PAUD Bengkulu City